Is the Survivorship of Birmingham Hip Resurfacing Better Than Selected Conventional Hip Arthroplasties in Men Younger Than 65 Years of Age? A Study from the Australian Orthopaedic Association National Joint Replacement Registry - Stoney, James (Clin Orthop Relat Res, 2020)
BACKGROUND: The Birmingham Hip Resurfacing (BHR) prosthesis is the most commonly used metal-on-metal hip resurfacing arthroplasty device. The current manufacturer-recommended target demographic for the BHR is male patients, younger than 65 years requiring a femoral head size of ≥ 50 mm. Female patients, older patients, and individuals with smaller femoral-head diameter (≤ 50 mm) are known to have higher revision rates. Prior studies suggest that the survivorship of the BHR when used in the target demographic is comparable with that of primary conventional THA, but comparing survivorship of the most durable hip resurfacing arthroplasty device to the survivorship of all conventional THA prostheses is not ideal because the THA group comprises a large number of different types of prostheses that have considerable variation in prosthesis survival. A more informative comparison would be with the THA implants with the best survivorship, as this might help address the question of whether survivorship in the BHR target population can be improved by using a well-performing conventional THA. QUESTIONS/PURPOSES: We compared the difference in cumulative percent revision, reasons for revision and types of revision for procedures reported to the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR) using the BHR prosthesis (femoral-head size > 50 mm) and three conventional THA prostheses identified as having the lowest 10-year cumulative percent revision in the currently recommended BHR target population to ask: (1) Does the BHR have a lower cumulative revision rate than the group of three conventional THA prostheses? (2) Is there a difference in the revision diagnosis between the BHR and the three best conventional THA prostheses? (3) What is the difference in the components used for a revision of a BHR compared with the three best conventional THA prostheses? METHODS: Data reported to the AOANJRR between September 1, 1999 and December 31, 2018 was used for this analysis. This study period includes almost the entire use of the BHR in Australia. The AOANJRR is a large national joint registry with almost 100% completeness, high accuracy, rigorous validation, and little to no loss to follow-up. The study population included males younger than 65 years that had received one hip replacement procedure for osteoarthritis. All patients with bilateral procedures, no matter the time interval between hips, were excluded. Only BHR prostheses with a femoral-head size ≥ 50 mm and conventional THA prostheses with femoral head sizes ≥ 32 mm and either ceramic-on-ceramic or metal, ceramic, ceramicized metal-on-crosslinked polyethylene (XLPE) bearings were included. These femoral head sizes and bearings were selected because they reflect modern conventional THA practice. There is no difference in the revision rate of these bearings in the AOANJRR. There were 4790 BHR procedures and 2696 conventional THA procedures in the study group. The mean (± SD) age for BHR procedures was 52 ± 7.8 years and 56 ± 7.1 years for conventional THA procedures. All comparative analyses were adjusted for age. Other demographics data including American Society Anesthesiologists (ASA) score and BMI were only included in AOANJRR data collection since 2012 and 2015, respectively, and have not been included in this analysis because of the low use of BHR in Australia since that time. The maximum follow-up was 18.7 years for both groups and mean follow-up of 11.9 years for the BHR and 9.3 years for the conventional THA group. Revision rates were determined using Kaplan-Meier estimates of survivorship to describe the time to the first revision, with censoring at the time of death or closure of the database at the time of analysis. A revision was defined as removal, replacement or addition of any component of a joint replacement. Revisions can be further classified as major revisions (removal of a component articulating with bone—usually the stem and/or the shell) or minor revisions (removal of other components—usually the head and/or the liner). The unadjusted cumulative percent revision after the primary arthroplasty (with 95% confidence intervals) was calculated and compared using Cox proportional hazard models adjusted for age. RESULTS: The BHR prosthesis had a statistically higher rate of all-cause revision at 17 years than the selected conventional THA prostheses (HR 2.77 [95% CI 1.78 to 4.32]; p < 0.001). The revision diagnoses differed between the groups, with the BHR demonstrating a higher revision rate for loosening after 2 years than the conventional THA protheses (HR 4.64 [95% CI 1.66 to 12.97]; p = 0.003), as well as a higher fracture rate during the entire period (HR 2.57 [95% CI 1.24 to 5.33]; p = 0.01). There was a lower revision rate for infection for the BHR compared with the THA group in the first 5 years, with no difference between the two groups after this time. All revisions of the BHR were major revisions (such as, removal or exchange of the femoral and/or acetabular components) and this occurred in 4.5% of the primary BHR procedures. Major revision was the most common type of revision for primary THA accounting for 1.7% of all primary THA procedures. Minor revisions (head, inset or both) were undertaken in a further 0.6% of primary THA procedures. CONCLUSIONS: Given the increasing revision risk of the BHR compared with better-performing conventional THA prostheses in the target population, we recommend that patients be counseled about this risk. We suggest that a THA with proven low revision rates might be the better choice, particularly for patients who are concerned about implant durability. Well-controlled prospective studies that show appreciable clinically important differences in patient-reported outcomes and functional results favoring the BHR over conventional THA prostheses using modern bearings are needed to justify the use of the BHR in view of this revision risk. LEVEL OF EVIDENCE: Level III, therapeutic study.